Penerapan Pendekatan Konstruktivistik untuk Meningkatkan Kemampuan Pemahaman Matematika Siswa - Ratih Rahmawati; Firma Andrian (CV. Multi Kreasi Media, 2022)
Mathematics learning is often filled with students' difficulties in solving problems using mathematical concepts, especially in story problems, it indicates that students' mathematical understanding abilities are low. The purpose of this study was to determine the application of a constructivist approach to improve students' understanding of mathematics. The research method used is Classroom Action Research (CAR). The data collection technique uses observation techniques to determine whether the stages in the constructivist approach have been carried out correctly by the teacher, and test techniques are used to determine the increase in students' mathematical understanding abilities. The data analysis technique used qualitative and quantitative data analysis techniques. Qualitative analysis was used to analyze data about students' learning comprehension abilities. While quantitative analysis is used to describe the increase in student learning outcomes/understanding in relation to mastery of the material being taught. The results showed that the application of the constructivist approach could improve students' mathematical understanding skills with the percentage of post-test completeness in the first cycle of 50% and then increased to 66.7% in the second cycle. Keywords: Constructivistic Approach, Mathematics Comprehension Ability, Mathematical Concept